Analisis Pengelolaan Keuangan Entitas Nonlaba Pada Paroki Hati Tak Bernoda Santa Perawan Maria Tilang - Sola, Silivanus; Dekrita , Yosefina Andia; Jaeng , Wihelmina M. Yulia (Universitas Nusa Nipa Maumere, 2025)
This research aimed to analyze the financial management of a non-profit entity at the Parish of Hati Tak Bernoda Santa Perawan Maria Tilang and its compliance with ISAK 35. The research used a descriptive qualitative approach through interviews, observations, and documentation. The results indicated that the parish’s financial recording was carried out both manually and using the MYOB application; however, the reports produced were still basic and oriented toward profit-oriented business entities. The financial statements presented only include the statement of financial position and the income statement, while the cash flow statement, statement of changes in net assets, and notes to the financial statements have not been fully implemented. The main challenges faced were a limited understanding of non-profit accounting and adapting MYOB to comply with ISAK 35 standards.